An ICT-Based Extension Services’ Adoption Model for Public Extension Officers: A Case in Mali - Kante, Macire (Journal of Information Systems and Technology Management, 2021)
The realization of higher yield and therefore agricultural productivity cannot be achieved without information. That information is disseminated in developing countries, particularly Mali by government-led extension services. However, there are few (public) extension officers to disseminate that information. That makes the use of other means such as ICT one of the best way to disseminate the extension services. This paper, firstly, looked at the drivers and challenges of the adoption of ICT based extension services by public extension officers in Mali from the literature to propose a conceptual framework. Secondly, the study assessed the survey questionnaire and thirdly, evaluated the proposed model. A sequential exploratory research design was followed. It consisted of conducting indept-interviews with 12 key stakeholders (agricultural scientist, policymakers, IT professional and head of extension services) in Bamako and Koulikoro. These data were analysed using computer-assisted qualitative data analysis software (RQDA) to contextualise the proposed conceptual framework. Thereafter, a survey questionnaire was designed and administered to 21 public extension officers in in Bamako, Kati and Koulikoro. Quantitative Data was analysed using Partial Least Square Structural Equation Modelling with the aid of the software Smartpls 3.2.8. This study validated a questionnaire of 19 items out of 26 for the next phase of the study with more respondents. Additionnaly, the results revealed that Relative Advantage, High Cost, Compatibility, Complexity, ICT-Skills and Policy explained 48.4% of the variance of the adoption of ICT based extension services by public extension officers.